Determinants of dietary diversity among women of reproductive age in two different agro-ecological zones of Rongai Sub-County, Nakuru, Kenya - Gitagia, M.W.; Rose Chepchirchir Ramkat, D.M.M.; Termote, Céline; Covic, Namukolo M.; Cheserek, M.J. (SNF Swedish Nutrition Foundation, 2019)
This study demonstrated that the diets of women were of poor quality despite the differences in agro-ecological zones and availability of food from the farm.